The gut virome and the relevance of temperate phages in human health - Avellaneda-Franco, Laura; Dahlman, Sofia; Barr, Jeremy J. (Frontiers in Cellular and Infection Microbiology, 2023)
Alterations in the gut virome impact human health. Bacteriophages, viruses that infect bacteria, dominate the gut virome and are mainly composed by virulent and temperate phages. While virulent phages exclusively replicate within and lyse their bacterial host’s cell, temperate phages switch from an integrated state residing within their bacterial host’s chromosome to an induced free virion state via an induction event. How often do these induction events occur and what are their implications on gut homeostasis? Here, we summarize the current knowledge of the gut virome based on metagenomics and present how the proportion of induced temperate phages varies amongst individuals, age, and disease states. Finally, we highlight the importance of building upon classical culture-dependent techniques and sequencing approaches to improve our understanding of temperate phages to enable their potential therapeutic use.